1970
DOI: 10.1063/1.1659439
|View full text |Cite
|
Sign up to set email alerts
|

Production and Study of an Alkali Plasma with Negative Ions

Abstract: The method of contact ionization is used to produce a three-component plasma (Cs+, Cl-, e-) in the Q-device BARBARA using a beam of Cesium chloride. The end-plate temperature controls the concentration of Cl-, which can be varied in a wide range. The density of negative ions is obtained from the difference between the positive ion density given by a Langmuir probe and the electron density given by a microwave resonator. A high concentration of negative ions is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1970
1970
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…4 Experiments have been designed to test this theory by comparison of equilibrium densities and ion input flux. 5 "" 8 Rough agreement between theory and experiment has been found at high density, where there is no electrostatic potential to confine ions inside the plasma column. However, at low densities, where a potential barrier between plasma and hot surfaces should reduce the ion surface losses, the measured loss rates are more than an order of magnitude greater than predicted by theory 0 In this paper, we report the direct measurement, by means of a Langmuir-Taylor detector, of the escaping flux of recombined atoms from one hot tungsten end plate of the Q-3 machine in contact with cesium and potassium plasma.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…4 Experiments have been designed to test this theory by comparison of equilibrium densities and ion input flux. 5 "" 8 Rough agreement between theory and experiment has been found at high density, where there is no electrostatic potential to confine ions inside the plasma column. However, at low densities, where a potential barrier between plasma and hot surfaces should reduce the ion surface losses, the measured loss rates are more than an order of magnitude greater than predicted by theory 0 In this paper, we report the direct measurement, by means of a Langmuir-Taylor detector, of the escaping flux of recombined atoms from one hot tungsten end plate of the Q-3 machine in contact with cesium and potassium plasma.…”
Section: Introductionmentioning
confidence: 82%
“…On the basis of evidence obtained from plasma profiles, one group has concluded that the anomalous losses occur at the hot end plates. 18 Others, on the basis of measurements with radial ion flux collectors, tend to favor a radial loss interpretation. 19~21 From Fig.…”
Section: B Anomalous Plasma Lossesmentioning
confidence: 98%
See 3 more Smart Citations